Desastres climáticos, género y pobreza (Serie de Webinars NPS Initiative) - Hacia una reducción inclusiva del riesgo de desastres en Bolivia - Escalante, Luis Enrique (International Food Policy Research Institute, 2023)
These slides were presented on Dec. 6, 2023 NPS Colombia webinar in collaboration with the University of the Andes “Climate Disasters, Gender, and Poverty: Towards an Inclusive Reduction of Disaster Risk in Bolivia” During this seminar, Luis Escalante, a researcher at IFPRI, presented the study as part of the course “Policy Analysis Tools using General Equilibrium Models for Colombia” .